Howea forsteriana: Kentia Palm - Samar S. Shawaqfeh; Timothy Broschat (EDIS, 2015)
The kentia palm is considered one of the best interior palms for its durability and elegant appearance. The dark green graceful crown of up to three dozen leaves gives it a tropical appearance. Containerized palms can be used on a deck or patio in a shady location or the palm can be planted into the landscape. This revised 3-page fact sheet was written by Samar Shawaqfeh and Timothy Broschat, and published by the UF Department of Environmental Horticulture, January 2015. (Photo credit: T. K. Broschat)